Assessment of the Factors that Influence Land Use Transition in Epetedo, Lafiaji/Ebute, and Sandgrouse Communities From 2002-2022 - Ajakaiye, O. Olabisi; Adeyemi, A. Hafeezah; Jubril, I. Zakariyau (Transactions on Engineering and Computing Sciences, 2023)
Unregulated land use transition creates hostile environment. This study assessed factors that influences land use transition in Epetedo, Lafiaji/Ebute and Sandgrouse communities in Lagos Island. Ullman theory of spatial interaction was used to explain the interaction that exist among different land uses. Both qualitative and quantitative techniques were used in measuring the transition in land use from year 2002-2022. The study employed observation and survey method to facilitate the realization of the objectives of this study. The whole of the study area (33 Streets) was studied, using base map to delineate the study area; checklist of streets and house numbers were used to take inventory of land uses; and questionnaires were administered to collect data related to individual perception on the subject matter. The study revealed that majority of the respondents strongly agreed that population growth, higher economic return, increase in rental value, location, and specific priorities are the major factors responsible for land use transition with the mean score of 4.49, 4.13, 4.07, 3.74, 3.69 respectively. With the mean value of 2.33. This study concluded land use transition is influenced by physical, social, and economic factors. Policy measures on population growth; capacity building; and balancing between maximizing economic return on land and land use regulatory framework were recommended to curb unplanned land use changes.